Leksyka zwierzęca w prawnej odmianie języka na materiale "Speculum Saxonum" Pawła Szczerbica (XVI w.) = The animal lexix in a legal variation of the language on the material "Speculum Saxonum" by Paweł Szczerbic (16th century) - Jurewicz-Nowak, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article was to recreate the linguistic image of animals in "Speculum Saxonum" by Paweł Szczerbic (1581). The analysis uses the assumptions of cognitive theory. It is essential for a legally conditioned community to classify animals according to the criteria of freedom or belonging to humans. From this perspective, human behaviour towards people as animal owners is assessed.
Keywords: językowy obraz świata; leksyka zwierzęca; tekst prawny; "Zwierciadło Saskie"; Szczerbic, Paweł (1552-1609); linguistic picture of the world; animal lexis; legal text